APOSENTADORIA: O TRABALHO E O SENTIDO DE SUA CONTINUIDADE PARA O PROFESSOR DO ENSINO SUPERIOR - SILVA, VALQUIRIA OLIVEIRA DA (2017)
We live in a complex society in which the individual frequently only feels recognized as a person by his or her productivity. Retirement is a step that can represent some sort of rupture to a few people or even the loss of life’s meaning to others. This research proposes an investigation about the meaning of the work activity to retired professors of the higher education, from the following question: Could the meaning of the work activity to the professor be the propelling reason to his continuity even when retired? We reviewed the literature on Higher Education, on Work Activity, on Retirement and on Aging, having as core theoretical references Saviani (2010); Antunes (1999; 2009); Borges and Yamamoto (2004); Codo (1999); Tardiff (2002); Pimenta (1999); Debert (1997; 1999); and Neri (1991). To develop our field research we conducted interviews with 06 retired professors that currently teach on private Higher Education Institutions. The methodology chosen to the development of the study was based on life history, using narrative as a method and granting support on authors as Josso (2004); Souza (2005; 2006) and Passeggi (2006). The data analysis is based on the Content Analysis Methodology proposed by Demartini (2001). Three themes were built through content analysis of the acquired stories: work path, purpose and meaning of work and feelings towards retirement and its connections to aging. The results obtained by this study point that the purpose of the work is the propeller reason to the continuity of the work activity to the majority of the investigated professors, it is possible to infer from the analysis that the interviewers remain at work because they feel at full productivity capacity, it was observed that even though the incoming plays an important role to the survival of any working individual, it was not considered relevant in this case.